THE EFFECT OF PATERNALIST LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - TARIM, MEHVEŞ (MEHMET AKIF ERSOY UNIV, 2021)
The aim of this study is to examine the impact of paternalist leadership behaviors on organizational citizenship behavior. The sample of the study consists of 535 healthcare professionals working in a private hospital in Istanbul. Correlation Analysis and Simple Linear Regression Analysis were used to examine the relationship between the measured variables. As a result of the research, it was found that paternalist leadership has a positive and moderate effect on organizational citizenship behavior (r = 0.427, p <0.01) and 18.3% of the changes in organizational citizenship behavior are explained by paternalist leadership. Our study shows that paternalistic leadership has a significant impact on the organizational citizenship behavior of health workers. By exhibiting paternalistic leadership behavior, health administrators can enable health workers to display more organizational citizenship behavior.
Keywords: Paternalist Leadership; Organizational Citizenship Behavior; Health Personnel; Health Management